STRATEGI PENANGANAN LIMBAH INDUSTRI BATIK DI KOTA PEKALONGAN - Mahfudloh, Mahfudloh; Lestari, Hesti (Journal of Public Policy and Management Review, 2017)
Batik is Indonesia's cultural heritage which is recognized as a world cultural heritage. Pekalongan city as "the world city's of batik" is one of the biggest batik producers in Indonesia. The number of batik production in Pekalongan cause of water pollution because batik waste dumped directly into the river without being processed. River in Pekalongan city contaminated batik waste into black and smelled. Pekalongan Environmental Agency (BLH) employ different strategies to deal with its batik waste problems in Pekalongan. This type of research is descriptive qualitative method of collecting data through interviews, literature studies and documents. The method used in this research is SWOT analysis of the strategic environment which consists of analysis of internal and external environment. Strategy obtained from the SWOT analysis were then tested by using a litmus test to measure the level of strategizing based on the number of scores. Based on the research that has been done, conducted by BLH Pekalongan city is still less than the maximum. Constraints the strategy of batik industrial waste management in Pekalongan is the lack of communal IPAL capacity, inadequate number of human resources, inadequate budgets, and the low level of public awareness. Factors that encourage stratetegi batik waste handling can be exploited to overcome obstacles waste handling batik in Pekalongan. Based on the results of a litmus test strategy that has been done is suggested that the strategic programs that have been formulated can be implemented by BLH Kota Pekalongan in order to make improvements the strategy of batik industrial waste management in Pekalongan.